SAPROFIT AND PATHOGENIC FUNGI ISOLATED FROM PET CLINICS AND STORES IN BOGOR CITY WEST JAVA - PRIBADI, Eko Sugeng; Kadri, Febrina Suci Dwi; Wijayanti, Revi Esti; Deskiharto, Arman; Widodo, Setyo (Universitas Syiah Kuala, 2025)
The research aimed to observe the occurrence of dermatophyte and other fungal species in grooming rooms and on groomers' clothing in several pet clinics and pet shops in Bogor City West Java. Ten veterinary clinics and five pet stores served as the study sites for this investigation. Five plates containing growth media were placed at five points in each room. Clothing swabs were collected from groomers immediately before they initiated their daily work activities. The result showed ten genus/species identified in grooming room and 16 genus/species isolated from the groomer clothes. Fusarium sp. was the predominant fungal isolate in grooming rooms (24.39%), followed by Candida albicans (9.76%). Notably, Fusarium sp. was also detected on groomers' clothing at a prevalence of 20.00%. Other pathogenic isolates included Aspergillus flavus and A. fumigatus. Despite the routine use of quaternary ammonium compounds, glutaraldehyde, anionic surfactants, and the ectoparasiticide amitraz in facility hygiene protocols, these disinfectant regimens insufficient in controlling fungal contamination. These findings highlight potential gaps in current disinfection practices within pet care facilities.